Reaction zone formed during diffusion bonding of TiNi to Ti6Al4V using Ni/Ti nanolayers - Sónia Simoes (2013)
This study investigated the interfacial structure of solid state diffusion bonding of TiNi to Ti6Al4V using reactive Ni/Ti multilayer thin films. The TiNi and Ti6Al4V surfaces were modified by sputtering, by deposition of alternated Ni and Ti nanolayers, to increase the diffusivity at the interface. Bonding experiments were performed at 750, 800 and 900 A degrees C at a pressure of 10 MPa with a dwell time of 60 min. The reaction zone was characterized by high-resolution scanning and transmission electron microscopy. Joints free from porosity and cracks were produced with Ni/Ti reactive multilayer thin films. Several phases formed at the interface, ensuring the bonding of these alloys. The reaction zone was constituted by columnar grains of Ti2Ni and AlNi2Ti, close to the Ti6Al4V base material, and by alternate layers of Ti2Ni and TiNi equiaxed grains. The grain size decreased from Ti6Al4V to TiNi base materials. Nanometric grains were observed in the layers closest to the TiNi base material.